A Measurement Device for the Normal Spectral Emissivity of Materials Under Low-Temperature and Vacuum Conditions - Xufeng Liu; Zhenyuan Zhang; Guojin Feng (Applied Sciences)
Based on parallel light, a device for measuring sample emissivity under vacuum and low temperature was established. In this paper, a new emissivity measurement formula was designed, which replaces the derivation of Kirchhoff’s law of thermal radiation. The device is designed with a light-weight blackbody, an improved cooling speed, and an improved PID temperature control system to achieve a good temperature stability, close to 1 mK. The device is capable of measuring within a wavelength range of 4 μm to 16 μm. The results of the uncertainty assessment show that the uncertainty of the normal emissivity is better than 1.6% in the range of 4 μm to 7 μm, and better than 0.6% in the range of 7 μm to 14 μm (k = 1) at 0 °C.